Quality comparison of biodiesel produced from waste cooking oil of restaurant and domestic kitchen. Issue 1 (2nd January 2020) - Khan, Salma; Raza, Mahnoor; Nosheen, Asia; Naz, Rabia; Shah, Syed Muhammad Usman; Hassan, Muhammad Nadeem
ABSTRACT: Concerns on environmental change, high-energy costs, and diminishing oil reserves have compelled a robust interest for the exploration of alternative energy sources. Current study was aimed to prepare biodiesel from waste cooking oil collected from restaurant and domestic kitchen, and to compare their fuel properties. To obtain high yield of biodiesel, some important variables such as methanol to oil ratio, catalyst concentration, and reaction temperature were varied. Results showed that highest yield of biodiesel was obtained at 1.5% catalyst concentration by restaurant oil at 6:1 methanol/oil at 65°C. Acid value, free fatty acid content, specific gravity, and kinematic viscosity were in accordance to ASTM standards. Cloud and pour point for both the oils was less than 14°C. Flash point and cetane index of restaurant biodiesel samples were according to the standards proposed by ASTM. Restaurant waste oil biodiesel showed better fuel properties as compared to domestic waste oil and can be suggested as an effective environmental-friendly source for biodiesel production.